2020
DOI: 10.3390/plants9121734
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Genomic Simple Sequence Repeat (g-SSR) Markers and Their Validation for Genetic Diversity Analyses in Kalmegh [Andrographis paniculata (Burm. F.) Nees]

Abstract: Kalmegh (Andrographis paniculata (Burm. F.) Nees) is one of the most important medicinal plants and has been widely explored as traditional medicine. To exploit its natural genetic diversity and initiations of molecular breeding to develop novel cultivars or varieties, developments of genomic resources are essential. Four microsatellite-enriched genomic libraries—(CT)14, (GT)12, (AG)15 and (AAC)8—were constructed using the genomic DNA of A. paniculata. Initially, 183 recombinant colonies were screened for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…Thus, more detailed studies with larger sampling sizes from extended geographical regions could draw a concrete inference ( Sahoo et al., 2021 ). Previously, evaluation of genetic diversity among the geographically isolated germplasm of A.paniculata was carried out using various dominant molecular markers ( Lattoo et al., 2008 ; Minz et al., 2013 ; Tiwari et al., 2016 ; Kumar et al., 2020 ; Hiremath et al., 2020 ) the outcomes of which are in line with our results. However, in the present study, metabolic pathway specific EST-SSR markers were designed and used to determine the genetic diversity among twenty-four ecotypes of A. paniculata .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, more detailed studies with larger sampling sizes from extended geographical regions could draw a concrete inference ( Sahoo et al., 2021 ). Previously, evaluation of genetic diversity among the geographically isolated germplasm of A.paniculata was carried out using various dominant molecular markers ( Lattoo et al., 2008 ; Minz et al., 2013 ; Tiwari et al., 2016 ; Kumar et al., 2020 ; Hiremath et al., 2020 ) the outcomes of which are in line with our results. However, in the present study, metabolic pathway specific EST-SSR markers were designed and used to determine the genetic diversity among twenty-four ecotypes of A. paniculata .…”
Section: Discussionsupporting
confidence: 89%
“…Bayesian model-based population structuring considered individuals with a probability score of >0.80 as genetically pure and a score of<0.80 as admixed type ( Figure 6B ). Mixing of pure individuals with few admixed accessions was observed in both the populations derived from model-based study, which could be due to the breeding behavior of the studied plant ( Kumar et al., 2020 ). AMOVA and PCoA also explained substantial genetic diversity among the studied accessions of six agroecologically grouped populations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Population Structure analysis also showed differentiation among T. cordifolia , T. sinensis , and T. rumphii study based on g-SSR markers. Similar studies were also reported in medicinal plants like Andrographis paniculate [ 48 ]. The genomic SSR markers developed in T. cordifolia were found transferable in the species Tinospora rumphii and Tinospora sinensis .…”
Section: Discussionsupporting
confidence: 85%
“…The design of microsatellite (simple sequence repeat, SSR) markers is based on conserved nucleotide sequences on both sides of simple repeat sequences, and the polymorphism among alleles is reflected by detecting the difference in the number of repeats [16]. SSRs are widely distributed in the nuclear and organellar genomes of eukaryotes [17][18][19][20]. SSR markers are considered to be among the most ideal molecular markers for the study of plant genetics [14,18].…”
Section: Introductionmentioning
confidence: 99%